A novel method of using accelerometry for upper limb FES control. Issue 11 (November 2016) - Sun, Mingxu; Kenney, Laurence; Smith, Christine; Waring, Karen; Luckie, Helen; Liu, Anmin; Howard, David
Highlights: A novel method for using accelerometry for upper limb FES control is proposed. Method avoids the poor sensitivity at certain angles seen in existing methods. New method performed well in representative testing with stroke participants. Abstract: This paper reports on a novel approach to using a 3-axis accelerometer to capture body segment angle for upper limb functional electrical stimulation (FES) control. The approach calculates the angle between the accelerometer x -axis and the gravity vector, while avoiding poor sensitivity at certain angles and minimizing errors when true acceleration is relatively large in comparison to gravity. This approach was incorporated into a state-machine controller which is used for the real-time control of FES during upper limb functional task performance. An experimental approach was used to validate the new method. Two participants with different upper limb impairments resulting from a stroke carried out four different FES-assisted tasks. Comparisons were made between angle calculated from arm-mounted accelerometer data using our algorithm and angle calculated from limb-mounted reflective marker data. After removal of coordinate misalignment error, mean error across tasks and subjects ranged between 1.4 and 2.9°. The approach shows promise for use in the control of upper limb FES and other human movement applications where true acceleration is relatively small in comparison with gravity.